UV radiation in the south of Portugal - Salgueiro, Vanda (2015)
The solar ultraviolet (UV) radiation is an important environmental factor due to its effects on Earth’s photochemical and biological processes and thus its monitoring is an important task. In this work, UV indexes and doses, which are directly related with the solar erythemal (UVER) radiation levels, obtained in the south of Portugal from surface measurements are shown. On the other hand, UVER and the corresponding UV indexes, estimated from the relation between UVER and UVB, as well as the prediction scheme of the UV indexes are also presented.